PENGARUH PEMBERIAN PELATIHAN, FASILITAS DAN KOMPENSASI TERHADAP MOTIVASI KERJA PEGAWAI BADAN PENGELOLA KEUANGAN DAN ASET DAERAH KABUPATEN BATU BARA - Evi Rafda Aryani; Iin Erpianto; Ahmad Irwan Pulungan; Riono Asnan Lubis; Siti Saroh (JEKKP (Jurnal Ekonomi, Keuangan dan Kebijakan Publik), 2021)
The formulation of the problem in this study is: How is the effect of training, facilities and compensation on employee motivation. This study aims to determine the effect of training, facilities and compensation on employee motivation. With the Total Sampling technique, the sample in this study was 65 people. Training partially have a positive effect on employee work motivation; Facilities partially have a positive effect on employee work motivation; Compensation partially have a positive effect on employee work motivation; Training, facilities and compensation simultaneously have a positive and significant effect on employee work motivation.